ANALISIS ANTRIAN DALAM OPTIMALISASI SISTEM PELAYANAN KERETA API DI STASIUN PURWOSARI DAN SOLO BALAPAN - Siti Anisah; Sugito Sugito; Suparti Suparti (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2015)
Train is one of mass transportation’s mode in great demand by the people of Indonesia. Purwosari and Solo Balapan stations are place which often visited by the public to travel long distances by using the train from economy class, business and executive. With so many types of trains that pass through the station, so the queuing analysis needs to be done to find out how the train service system at the station. From the results obtained, the queuing model at the Purwosari station is (M/M/2):(GD/∞/∞) for model lanes of 1 and 4 and lanes of 2 and 3. For the queuing model from lanes of 1 and 5 in the Solo Balapan station obtained models (M/M/2):(GD/∞/∞). Later models of queuing lanes of 2,3, and 4 at the station Solo Balapan is (M/M/3):(GD/∞/∞), while lane of 6 is (M/M/1):(GD/∞/∞). Keywords: Train, Purwosari and Solo Balapan Stations, Queuing models.